Editorial - Kumar M, Dr Rupesh (Ushus Journal of Business Management, 2021)
Ushus Journal of Business Management wishes all its readers a Happy New Year!In this final issue of 2016, we bring to you two intellectually stimulating research articles and two enlightening case studies that give us new insights into marketing.India is one of the fastest growing economies and a bright spot in an otherwise gloomy world economy with double-digit growth in many sectors like FMCG, Consumer Durables, Fashion, Passenger cars, etc. In the first article of this issue focuses on consumer durables. Consumer durables market is valued at 12.5 billion USfor the year 2015 (IBEF Report, 2016). In the consumer durablemarket the key element is trust towards a brand or a reseller. Keeping this in mindthis research focuses on the trust factor in selling of the non-essential consumer durable products like‘cosmetics.’ The author, Suhan, has utilized the path coefficient threshold values to measure between indicators namely, cause purview and emotional benefits, cause consequential and trust, cause rubric and trust, cause span and emotional benefits, emotional benefits and trust, functional benefits and trust, ability and trust, benevolence and trust. Therefore the corporates need to make a moderate effect model to substantial effect by strengthening cause campaigns like the fight against animal testing, support community trade, defend human rights, activate self-esteem and protect the planet by taking environmental issues.